GREEN ACCOUNTING : IMPLEMENTASI TRI HITA KARANA DALAM MEMBANGUN EKONOMI DESA YANG BERKELANJUTAN - Ni Kadek Cahya Dwi Utami; Made Andy Pradana Sukarta; I Gede Dirga Surya Arya Widhyadanta; I Nyoman Darmayasa (Faculty of Economics and Business, Universitas Warmadewa, 2026)
Sustainable village economic development requires a balance between economic, social, and environmental dimensions. This study analyzes the role of the Village Credit Institution (LPD) of Canggu in integrating Green Accounting with the local philosophy of Tri Hita Karana. Using a qualitative case study design, data were collected through in-depth interviews, documentation, and triangulation involving supervisors, managers, and clients of the LPD. The findings reveal that the values of Parahyangan, Pawongan, and Palemahan are embedded in LPD practices through support for religious rituals, social welfare programs, and environmentally friendly initiatives. This integration strengthens the implementation of Green Accounting and fosters village development rooted in local culture. The study highlights the contribution of LPD as an inclusive and sustainable traditional financial institution aligned with the Triple Bottom Line framework.